Secondary Hip Osteoarthritis due to Neurofibroma Treated with Total Hip Replacement. (23rd October 2012) - Tangsataporn, Suksan; Shakib, Alireza; Kuzyk, Paul R.; Backstein, David J.; Gross, Allan E.; Safir, Oleg A.
Abstract : Background . Local plexiform neurofibroma can lead to deformity of the pelvis, valgus deformity of femoral neck, and joint capsule laxity. We report a case of secondary hip osteoarthritis with subluxation and coxa vara deformity resulting from an extra-articular neurofibroma treated with total hip replacement. Case Description . A 39-year-old man had a large benign plexiform neurofibroma at buttock which induced secondary osteoarthritis of the hip. Conservative treatment of tumor was selected because the patient had low chance of malignant transformation due to absence of other neurofibromatosis features. However, due to secondary osteoarthritis he underwent total hip arthroplasty. Anterior capsulotomy was selected to avoid large posterior hip tumor mass. In order to avoid the difficulties associated with setting tension of the abductor muscle, modified trochanteric slide osteotomy with trochanteric advancement, lateralized cup placement, and extended neck offset were used. One year after the surgery, the patient had excellent clinical function, hip stability, leg length equality and was satisfied with the outcome. Clinical Relevance . We concluded that the modified trochanteric slide osteotomy with trochanteric advancement represents a valuable approach for THR in patients with extremely elongation of the hip abductor and secondary hip osteoarthritis resulting from extra-articular neurofibroma.